Immigration Restrictions as Active Labor Market Policy: Evidence from the Mexican Bracero Exclusion - Clemens, Michael A.; Lewis, Ethan G.; Postel, Hannah M. (American Economic Review, 2018)
An important class of active labor market policy has received little impact evaluation: immigration barriers intended to raise wages and employment by shrinking labor supply. Theories of endogenous technical advance raise the possibility of limited or even perverse impact. We study a natural policy experiment: the exclusion of almost half a million Mexican bracero farm workers from the United States to improve farm labor market conditions. With novel labor market data we measure state-level exposure to exclusion, and model the absent changes in technology or crop mix. We fail to reject zero labor market impact, inconsistent with this model. (JEL J15, J18, J22, J31, J43, J61, O33)